Kolaborasi Ekotoksikologi-Toksikologi Untuk Meningkatkan Kesadaran Lingkungan Di Kampung Batik Laweyan: Aspek Ekotoksikologi - Margareta Novian Cahyanti; Sri Hartini; Dewi K.A. Kusumahastuti; November R. Aminu; Indah T Susilowati; Noviana Dewi; Diki Anggaran; Vincentia N. P. Kristanti; F.D. Cahyo; K Saputri (CV. ITTC INDONESIA, 2025)
Dye waste, whether derived from synthetic or natural substances, can pollute the environment if not properly managed. This pollution can degrade the quality of water, soil, and nearby ecosystems. In Kampung Batik Laweyan, one of the well-known batik centers in the Surakarta area, improper waste management poses a serious threat to the sustainability of the batik industry and the health of the surrounding community. A major issue lies in the lack of awareness and understanding about the ecotoxicological effects of dye waste, particularly synthetic dyes, which often contain heavy metals and harmful chemicals. This community service activity was initiated to address this issue through education and empowerment. The main objective was to increase knowledge about the environmental and health hazards posed by dye waste. Activities included health check-ups, questionnaire distribution to assess baseline understanding, educational sessions on ecotoxicology, and practical training on the use of batik brushes. This training aimed to reduce direct skin exposure to harmful substances and minimize the overuse of dyes during the batik-making process. The results showed a significant improvement in participants’ awareness of the risks associated with synthetic dyes, including heavy metal exposure and their long-term effects on aquatic life and soil organisms. Participants also gained better insight into sustainable waste management practices. In conclusion, the program successfully raised awareness and encouraged more responsible behavior among batik artisans. It is hoped that such initiatives can continue to promote environmentally friendly practices in the traditional batik industry, contributing to a healthier ecosystem and safer working conditions.